Awareness on standard precautions among auxiliary nurse midwives in a subdivision of Purba Bardhaman district, West Bengal - Mollah, Azharuddin; Ray, Soumalya; Shrivastava, Prabha; Das, Dilip Kumar (International Journal Of Community Medicine And Public Health, 2019)
Background: Due to their occupation, health workers are always at-risk of developing life-threatening infections. “Standard precautions” acts as a protective barrier against this. There is a lack of information about awareness on standard precaution among auxiliary nurse midwives (ANMs), the frontline health personnel working at Sub-centres. The aim of the study was to assess the current awareness on Standard precautions among ANMs. Methods: This descriptive study with cross-sectional design was conducted at sub centre level of Bardhaman Sadar North subdivision, Purba Bardhaman district, West Bengal. In this study, conducted between September-November 2017, three blocks were chosen from the seven blocks in the subdivision through simple random sampling. All ANMs working in these blocks were approached and data were collected on background characteristics and knowledge on key elements of Standard precautions using a pre-tested and pre-designed self-administered questionnaire. Items assessing standard precaution were scored one (for correct response) and zero (for incorrect/missed response). Maximum possible score was fourteen and minimum was zero. Statistical analysis used association of acceptability of knowledge with background characteristics were assessed using bivariate analysis and binary logistic regression. Results: Median (IQR) of the score obtained was 10 (9, 12). Out of total 138 subjects, 64.5% had acceptable knowledge (score ≥10) regarding standard precautions. Participants’ age had a statistically significant association with acceptable knowledge in the bivariate analysis; however, in the final model, only training status of the participants remained significant [AOR-0.304 (0.098-0.938)]. Conclusions: It emphasized the importance of regular training on Standard precautions for ANMs.